Changing faces of mitochondrial disease: autosomal recessive POLG disease mimicking myasthenia gravis and progressive supranuclear palsy. Issue 2 (8th December 2022) - Elwan, Menatalla; Schaefer, Andrew M; Craig, Kate; Hopton, Sila; Falkous, Gavin; Blakely, Emma L; Taylor, Robert W; Warren, Naomi
Abstract : Background: Mitochondrial disorders are known to cause diverse neurological phenotypes which cause a diagnostic challenge to most neurologists. Pathogenic polymerase gamma ( POLG ) variants have been described as a cause of chronic progressive external ophthalmoplegia, which manifests with ptosis, horizontal and vertical eye movement restriction and myopathy. Autosomal dominant progressive external ophthalmoplegia is rarely associated with Parkinsonism responsive to levodopa. Methods: We report a case of a 58-year-old man who presented with an eye movement disorder then Parkinsonism who made his way through the myasthenia then the movement disorder clinic. Results: A diagnostic right tibialis anterior biopsy revealed classical hallmarks of mitochondrial disease, and genetic testing identified compound heterozygous pathogenic gene variants in the POLG gene. The patient was diagnosed with autosomal recessive POLG disease. Conclusions: It is important to maintain a high index of suspicion of pathogenic POLG variants in patients presenting with atypical Parkinsonism and ophthalmoplegia. Patients with POLG -related disease will usually have ptosis, and downgaze is typically preserved until late in the disease. Accurate diagnosis is essential for appropriate prognosis and genetic counselling.